Carreira de modelo: formatos de imersão, habilidades profissionais e recursos de ascensão - Cruz, Karina Garcia Santos (2020)
This research is based on the thesis that, through the study of the modeling career, it is possible to unveil a myriad of phenomena related to the investigation of women's crafts, to the direct influence of the Patriarchate and religious institutions on the control of women's capacities, of how these agreements limited the insertion of women in the participation of the productive economy and dispute for equitable rights, to the control of the female body, to the subcondition of women in the most diverse spheres that make up the chain of this universe, in a paradoxical sense, as it provided the limited freedom of entry in the world. Labor market. The focus on the modeling career, more specifically, the overriding objective of understanding the reasons for insertion of the female group in the world of fashion, the strategies and development of the skills of permanence and consecration, is relationally merged with the approaches mentioned for the explanation of the process of insertion of women in the Labor Market, the introjection of symbolic codes for professional development, elaboration of strategies to deviate from risk situations, among others. In view of these reasons, the research deals, at first, with the traditions generated in the Sociology of Professional Groups with a focus on dialogue with the model career, the process of insertion of women in the Labor Market with an emphasis on Patriarchal influence, female engagement and emancipation process. The second moment focuses on the relationship between the body and the clothes, the symbols of power and status that unite, identify and segregate from social classes, in the control devices of female bodies, in the subordinate participation of women in the manufacture of clothes, in exploitation of female labor. The third moment analyzes the intersections between fashion and the universes of art, consumption, in the formation of beauty standards. Attention is given to the reading and interpretation of symbologies, to fashion capitalism, to the plastic process of changes in the female body to fit the body of fashion. The fourth moment specifically analyzes the agencies, understood as responsible for the transmission of learning and development of models, illustrates the format of organization, division of professional activities, the grammar and deontology of the practices that produce this world. It analyzes how activities in the illicit world are orchestrated, the underworld of models that borders on luxury prostitution. The fifth moment presents the composition of the empirical universe made up of models that have varied positions and experiences in the profession. Through interviews, observations, notes in the field diary, documentaries and readings about the career, the results of the crucial questions that motivated this research work, concerning the reasons for insertion, the strategies and skills of maintenance and ascension are obtained and analyzed. Among the results, I highlight the immersion of the female public motivated by reasons of the production of the professional fetish, through friendship networks; the permanence of the career due to variables that involve mastery of symbolic codes, body hexis, charisma, competence in the use of Communication and Information Technologies (ICTs) and social networks for building the portfolio and personal marketing, strategies for deviating situations risk; and the rise with a focus on internationalization through the acquisition of foreign language learning, with an emphasis on English, in addition to the sum of the social resources acquired during the trajectory of professional socialization.